Carbon nanotube dispersion and preparation method thereof

By using a dispersant containing N atoms and a compound of sulfonic acid group, hydroxyl group and aromatic ring, carbon nanotube dispersion with excellent dispersion and low viscosity is prepared, which solves the problems of low dispersion of carbon nanotubes in the electrode and the increase in viscosity over time, and improves the performance of the lithium secondary battery electrode.

CN119855784APending Publication Date: 2025-04-18LG CHEM LTD

Patent Information

Application Number
CN202480003893.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-23
Filing Date
2024-02-22
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The carbon nanotubes have low dispersion and aggregation due to high specific surface area and van der Waals forces in the electrode, and the mechanical dispersion treatment method has the problem of increasing viscosity over time.

Method used

A dispersant containing N atoms and a compound containing sulfonic acid groups, hydroxyl groups and aromatic rings in the molecular structure are used as dispersants to prepare carbon nanotube dispersions through mixing and dispersing treatment to improve its dispersion and stability.

Benefits of technology

The excellent dispersion, low viscosity and viscosity of carbon nanotube dispersion are achieved with small changes over time, and are suitable for electrode materials for lithium secondary batteries, improving the conductivity and performance stability of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005299782040000171
    Figure BDA0005299782040000171
  • Figure BDA0005299782040000181
    Figure BDA0005299782040000181
Patent Text Reader

Abstract

The present invention relates to a carbon nanotube dispersion comprising carbon nanotubes, a dispersant and a dispersion medium, in which the dispersant comprises a first dispersant and a second dispersant in a weight ratio of 100: 10 to 100: 90, the first dispersant being a dispersant containing N atoms, the second dispersant being a dispersant containing N atoms, and the dispersion medium being a dispersant containing N atoms. The second dispersant is a compound containing a sulfonic acid group, a hydroxyl group, and an aromatic ring in a molecular structure, and a weight ratio of the carbon nanotubes to the dispersant is 100: 50 to 100: 500, thereby having a low viscosity and a small change in viscosity over time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0024182 filed in the Korean Intellectual Property Office on February 23, 2023, the contents of which are incorporated herein by reference. Technical Field

[0004] The present invention relates to a carbon nanotube dispersion and a method for preparing the same, and more particularly to a carbon nanotube dispersion having low viscosity and little change in viscosity over time and a method for preparing the same. Background Art

[0005] With the development of technology and the increase in demand for mobile devices, the demand for secondary batteries as energy sources is increasing rapidly. Among secondary batteries, lithium secondary batteries with high energy density, high voltage, long cycle life and low self-discharge rate have entered commercial use and are widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, methods for increasing electrode density and manufacturing electrodes with higher energy density per unit volume are being actively studied.

[0006] Generally, high-density electrodes are formed by molding electrode active material particles with a size of several μm to tens of μm by high-pressure pressing. During the molding process, the particles are deformed, the space between the particles may be reduced, and the electrolyte permeability may be easily deteriorated.

[0007] In order to solve the above problems, a conductive material with excellent conductivity and strength is used when manufacturing electrodes. Although the conductive material is arranged between the electrode active materials and undergoes a molding process, the micropores between the active material particles are maintained so that the electrolyte can be easily infiltrated, and the conductivity is excellent so that the resistance in the electrode can be reduced. Among the conductive materials, the use of carbon nanotubes is increasing, and the carbon nanotubes are fibrous carbon-based conductive materials that can further reduce the electrode resistance by forming a conductive path in the electrode.

[0008] Carbon nanotubes (a type of fine carbon fiber) are tubular carbon fibers with a diameter of 1 μm or less, and are expected to be used and commercialized in various fields due to their high electrical conductivity, high tensile strength, and heat resistance due to their specific structure. However, carbon nanotubes have problems such as low dispersibility and the occurrence of aggregation due to strong van der Waals attraction between carbon nanotubes due to their high specific surface area.

[0009] In order to solve the above problems, a method of dispersing carbon nanotubes in a dispersion medium by mechanical dispersion treatment such as ultrasonic treatment has been proposed. However, in the case of the mechanical dispersion treatment method, there is a problem in that the carbon nanotubes aggregate as soon as the ultrasonic irradiation is terminated.

[0010] Therefore, there is a need to develop a method for preparing a carbon nanotube dispersion which can improve the dispersibility of carbon nanotubes, have a low viscosity, and suppress an increase in viscosity over time. Summary of the invention

[0011] Technical issues

[0012] The present invention solves the above problems and provides a carbon nanotube dispersion having excellent dispersibility, low viscosity and little change in viscosity over time by comprising a dispersant containing an N atom and a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure.

[0013] In addition, the present invention provides a negative electrode slurry composition for a lithium secondary battery, which includes the carbon nanotube dispersion.

[0014] Furthermore, the present invention provides a method for preparing the carbon nanotube dispersion.

[0015] Technical Solution

[0016] In order to achieve the above-mentioned object, the present invention provides a carbon nanotube dispersion.

[0017] [1] The present invention provides a carbon nanotube dispersion comprising carbon nanotubes, a dispersant and a dispersion medium, wherein the dispersant comprises a first dispersant and a second dispersant in a weight ratio of 100:10 to 100:90, the first dispersant is a dispersant containing N atoms, the second dispersant is a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in its molecular structure, and the weight ratio of the carbon nanotubes to the dispersant is 100:50 to 100:500.

[0018] [2] The present invention provides a carbon nanotube dispersion according to [1], wherein the carbon nanotube has a specific surface area (BET) of 800 m 2 / g or greater.

[0019] [3] The present invention provides the carbon nanotube dispersion according to [1] or [2], wherein the carbon nanotubes are single-walled carbon nanotubes.

[0020] [4] The present invention provides the carbon nanotube dispersion according to any one of [1] to [3], wherein the carbon nanotubes are contained in an amount of 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the carbon nanotube dispersion.

[0021] [5] The present invention provides a carbon nanotube dispersion according to any one of [1] to [4], wherein the first dispersant is one or more selected from the following: polyvinyl pyrrolidone, polyacrylic acid hydrazide, poly-N-vinyl-5-methyl Oxazolidinone, N-alkylpolyimine, N-acetylpolyimine, polyacrylamide, poly-L-lysine hydrobromide, benzyl-dodecyl-dimethylammonium chloride and polyethyleneimine.

[0022] [6] The present invention provides the carbon nanotube dispersion according to any one of [1] to [5], wherein the second dispersant is a lignin sulfonate compound.

[0023] [7] The present invention provides the carbon nanotube dispersion according to any one of [1] to [6], wherein the second dispersant is sodium lignin sulfonate, calcium lignin sulfonate, or a mixture thereof.

[0024] [8] The present invention provides the carbon nanotube dispersion according to any one of [1] to [7], wherein the dispersant comprises the first dispersant and the second dispersant in a weight ratio of 100:20 to 100:80.

[0025] [9] The present invention provides the carbon nanotube dispersion according to any one of [1] to [8], wherein the weight ratio of the carbon nanotube to the dispersant is 100:100 to 100:300.

[0026]

[10] The present invention provides the carbon nanotube dispersion according to any one of [1] to [9], wherein the weight ratio of the carbon nanotubes to the dispersant is 100:120 to 100:250.

[0027]

[11] The present invention provides a carbon nanotube dispersion according to any one of [1] to

[10] , wherein the dispersion medium is one or more selected from the following: an amide-based polar organic solvent, an alcohol-based solvent, a glycol-based solvent, a glycol ether-based solvent, a ketone-based solvent, an ester-based solvent and an aqueous solvent.

[0028]

[12] The present invention provides the carbon nanotube dispersion according to any one of [1] to

[11] , wherein the viscosity of the carbon nanotube dispersion is 1,000 cP to 16,000 cP.

[0029] Furthermore, in order to solve another task, the present invention provides an electrode slurry composition for a lithium secondary battery, which comprises the carbon nanotube dispersion.

[0030]

[13] The present invention provides an electrode slurry composition for a lithium secondary battery, the composition comprising the carbon nanotube dispersion according to any one of [1] to

[12] and an electrode active material.

[0031] Furthermore, in order to achieve another object, the present invention provides a method for preparing a carbon nanotube dispersion.

[0032]

[14] The present invention provides a method for preparing a carbon nanotube dispersion of any one of [1] to

[12] , the method comprising: (1) a step of mixing carbon nanotubes, a dispersant and a dispersion medium to prepare a mixture; and (2) a step of dispersing the mixture, wherein the dispersant comprises a first dispersant and a second dispersant in a weight ratio of 100:10 to 100:90, the first dispersant is a dispersant containing N atoms, the second dispersant is a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in its molecular structure, and the weight ratio of the carbon nanotubes to the dispersant is 100:50 to 100:500.

[0033] Beneficial Effects

[0034] The carbon nanotube dispersion of the present invention contains both a dispersant containing N atoms and a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure, and has excellent carbon nanotube dispersibility, low viscosity and little change in viscosity over time, and is therefore advantageous in terms of storage and use of the carbon nanotube dispersion. DETAILED DESCRIPTION

[0035] The words or terms used in this specification and claims should not be interpreted as the meanings defined in common dictionaries. The words or terms should be interpreted as having meanings consistent with the technical concept of the present invention based on the fact that the inventor can appropriately define the meanings of the words or terms to best illustrate the principles of the present invention.

[0036] The terms used in this specification are for the purpose of describing exemplary embodiments only and are not intended to limit the present invention. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.

[0037] In the present specification, terms such as "comprising", "including" and "having" are intended to indicate the presence of implemented features, numbers, steps, components or combinations thereof, and it should be understood that the terms do not exclude the possibility of the presence or addition of one or more other features, numbers, steps, components or combinations thereof.

[0038] In the present specification, "%" means weight % unless otherwise specifically stated.

[0039] In this specification, the average particle size "D 50 ” means the particle size corresponding to 50% cumulative volume, and “D 90 ” means the particle size corresponding to 90% cumulative volume. 50 ” and “D 90"It can be measured using, for example, laser diffraction. Laser diffraction is generally capable of measuring particle sizes in the submicron range to several millimeters, and can obtain results with high reproducibility and high resolution.

[0040] In the present specification, the "specific surface area" is measured by the BET method, and specifically can be calculated from the nitrogen absorption at liquid nitrogen temperature (77K) using BELSORP-mino II of BEL of Japan.

[0041] Hereinafter, the present invention will be described in detail.

[0042] The carbon nanotube dispersion according to the present invention is a carbon nanotube dispersion comprising carbon nanotubes (CNT), a dispersant and a dispersion medium, wherein the dispersant comprises a first dispersant and a second dispersant in a weight ratio of 100:10 to 100:90, the first dispersant is a dispersant containing N atoms, the second dispersant is a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in its molecular structure, and the weight ratio of the carbon nanotubes to the dispersant is 100:50 to 100:500.

[0043] Carbon Nanotube Dispersion

[0044] Hereinafter, each component of the carbon nanotube dispersion of the present invention will be described in detail.

[0045] (1) Carbon nanotubes

[0046] The term "carbon nanotube" used in the present invention is a secondary structure formed by aggregating carbon nanotube units in whole or in part to form a bundle, and the carbon nanotube units have a cylindrical graphene sheet with a diameter of nanometer size and have sp 2 Bonding structure. In this case, depending on the angle and structure of the rolled graphene sheet, it can exhibit the characteristics of a conductor or a semiconductor. Based on the number of bonds forming the wall, carbon nanotube units can be divided into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT) and multi-walled carbon nanotubes (MWCNT).

[0047] The term "bundle type" used in the present invention refers to a secondary shape of a bundle type or a rope type, in which a plurality of carbon nanotube units are arranged in parallel, wherein the axes of the length direction of the units are arranged in substantially the same direction, or twisted or tangled after the arrangement. "Non-bundle type or tangled type" refers to a tangled type of carbon nanotube units without a specific shape such as a bundle type or a rope type.

[0048] Carbon nanotubes have high conductivity, but have high cohesion due to the van der Waals forces existing between carbon nanotubes. If the conductive material aggregates, a conductive path may not be properly formed, and relatively more conductive material is used, which reduces the amount of active material and deteriorates the performance of the electrode. Therefore, it is difficult to commercialize carbon nanotubes as a conductive material.

[0049] The carbon nanotube dispersion according to the present invention contains a dispersant containing a N atom and a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure, and can suppress the change in viscosity of the carbon nanotube dispersion over time, thereby showing a low viscosity increase rate and showing favorable effects in storing and using the carbon nanotube dispersion.

[0050] In addition, if the carbon nanotube dispersion according to the present invention is applied to prepare electrode slurry, the carbon nanotubes are uniformly located between active materials, and during the preparation of electrodes by coating the electrode slurry and drying and rolling it, the minute spaces between the electrode active materials can be kept constant. In addition, since the carbon nanotubes are uniformly distributed without aggregation, a conductive path can be sufficiently formed with a small amount of carbon nanotubes.

[0051] The carbon nanotube dispersion according to one embodiment of the present invention may include one or more of single-walled carbon nanotube units, double-walled carbon nanotube units, and multi-walled carbon nanotube units, and specifically include single-walled carbon nanotubes (SWCNTs).

[0052] The specific surface area (BET) of carbon nanotubes can be 800 m 2 / g or more, in particular, a specific surface area (BET) of 800m 2 / g to 2000m 2 / g. Since the carbon nanotube dispersion of the present invention contains both a dispersant containing N atoms and a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure, it exhibits excellent dispersibility, and therefore, for a carbon nanotube having a molecular weight of 800 m 2 / g or more of a high specific surface area (BET) carbon nanotube can exhibit excellent dispersibility, the carbon nanotube dispersion can exhibit low viscosity, and can exhibit the effect of small change in viscosity over time.

[0053] The carbon nanotube may be included at 0.1 to 5 parts by weight, specifically 0.2 to 3 parts by weight, more specifically 0.4 to 2 parts by weight, based on 100 parts by weight of the conductive material dispersion.

[0054] Since the carbon nanotube dispersion according to one embodiment of the present invention includes a dispersant with excellent dispersibility, excellent dispersibility can be exhibited for carbon nanotubes with high specific surface area, and carbon nanotubes with high specific surface area can be uniformly dispersed. The carbon nanotube dispersion can have a high content of carbon nanotubes such as the above range compared to conventional commonly used carbon nanotube dispersions. If a carbon nanotube dispersion with a low carbon nanotube content is used to prepare an electrode slurry, the solid content of the prepared electrode slurry may be reduced, the thickness (wet thickness) after coating the electrode slurry and before drying may become thicker, and the rolling ratio measured after subsequent drying and rolling treatment may become higher, which may result in a large difference in thickness ratio before and after drying and rolling. Like this, if the rolling ratio increases, the components in the slurry containing the positive active material may be damaged during processing, and defects that deteriorate the performance of the electrode may occur.

[0055] (2) Dispersant

[0056] The carbon nanotube dispersion according to the present invention contains both a first dispersant and a second dispersant as dispersants for improving the dispersibility of carbon nanotubes at a weight ratio of 100:10 to 100:90. In addition, the first dispersant is a dispersant containing N atoms, and the second dispersant is a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure.

[0057] The dispersant containing N atoms included as the first dispersant and the compound containing sulfonic acid groups, hydroxyl groups and aromatic rings in the molecular structure included as the second dispersant are dispersants in the carbon nanotube dispersion. They play a role in improving the dispersibility of the carbon nanotubes and can show the effect of suppressing the viscosity increase and viscosity change over time of the carbon nanotube dispersion.

[0058] In particular, in addition to the dispersant containing N atoms as the first dispersant, the carbon nanotube dispersion according to the present invention further contains a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure as a second dispersant, and can exhibit excellent dispersibility compared to a carbon nanotube dispersion containing only a conventional commonly used dispersant, and can exhibit low particle aggregation, low sedimentation rate, low viscosity and excellent adhesion to the separator substrate of the slurry composition.

[0059] Since the second dispersant contains sulfonic acid group, hydroxyl group and aromatic ring in its molecular structure, the viscosity of carbon nanotube dispersion, especially aqueous carbon nanotube dispersion, can be reduced due to the bulky structure of the compound and the influence of sulfonic acid group and hydroxyl group, and the increase of viscosity over time can be significantly improved.

[0060] As the first dispersant, a dispersant containing an N atom can be used, and if a dispersant containing an N atom in the structure, i.e., a specific dispersant containing an amine structure, an amide structure, an imine structure, an ammonium structure, etc., is applied as the first dispersant, a further improved viscosity improvement effect and an effect of suppressing the change in viscosity over time can be exhibited. The dispersant containing an N atom can be dissolved in water, and can be, for example, one or more selected from the following: polyvinyl pyrrolidone, polyacrylic acid hydrazide, poly-N-vinyl-5-methyl Oxazolidinone, N-alkylpolyimine, N-acetylpolyimine, polyacrylamide, poly-L-lysine hydrobromide, benzyl-dodecyl-dimethylammonium chloride and polyethyleneimine.

[0061] In addition, as the second dispersant, a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure can be used, and the compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure can be a lignin sulfonate compound. The second dispersant can be, for example, sodium lignin sulfonate, calcium lignin sulfonate, or a mixture thereof.

[0062] If the dispersant includes a dispersant containing N atoms as the first dispersant and a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure as the second dispersant, the interaction between the aromatic ring in the carbon nanotube dispersion and the carbon nanotubes and the interaction of hydrogen bonds between the hydroxyl group and the polymer dispersant can be properly balanced, and the effect of reducing the viscosity of the carbon nanotube dispersion and suppressing the increase in viscosity over time can be exhibited. In addition, the sulfonic acid group presenting a negative charge can induce an electrostatic shielding effect and can suppress the aggregation between carbon nanotubes.

[0063] The dispersant includes the first dispersant and the second dispersant in a weight ratio of 100:10 to 100:90, specifically, may include the first dispersant and the second dispersant in a weight ratio of 100:10 to 100:80 or 100:20 to 100:80, more specifically, in a weight ratio of 100:20 to 100:50. If the carbon nanotube dispersion includes the first dispersant and the second dispersant in the weight ratio as the dispersant, the carbon nanotubes can be uniformly dispersed in the carbon nanotube dispersion, and the viscosity can be low, and the viscosity can be maintained at a certain level over time.

[0064] The weight ratio of the carbon nanotubes to the dispersant may be 100:80 to 100:500, specifically 100:100 to 100:400, 100:100 to 100:300, 100:100 to 100:250, 100:120 to 100:300, or 100:120 to 100:250, more specifically 100:120 to 100:200.

[0065] If the dispersant is excessively contained beyond the range, the conductivity of the electrode may be suppressed due to the excessive dispersant if the carbon nanotube dispersion is applied to an electrode, and the dispersant may act as an impurity in the electrode. On the contrary, if the dispersant is contained in a small amount compared with the range, the dispersibility improvement effect, the viscosity reduction effect, and the effect of suppressing the change in viscosity over time may become insufficient.

[0066] (3) Dispersion medium

[0067] The dispersion medium is a dispersion medium for dispersing the carbon nanotubes and the dispersant, and mainly disperses the carbon nanotubes to provide as a carbon nanotube dispersion in order to prevent aggregation when the powder type carbon nanotubes are applied as they are to the electrode slurry composition.

[0068] The dispersion medium may be one that can dissolve or disperse the carbon nanotubes and the dispersant at a certain level or higher. The dispersion medium may be included in an amount that allows the electrode slurry composition to have a suitable viscosity in consideration of the coatability of the electrode slurry composition subsequently prepared using the carbon nanotube dispersion.

[0069] The dispersion medium may use any one commonly used in the art for the purpose of dispersing carbon nanotubes and dispersants, but is not particularly limited, and may be, for example, at least one selected from amide-based polar organic solvents, alcohol-based solvents, glycol-based solvents, glycol ether-based solvents, ketone-based solvents, ester-based solvents, and aqueous solvents.

[0070] The amide-based polar organic solvent may be one or more selected from dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), 3-methoxy-N,N-dimethylpropionamide (Equamide M100, a product of idemitsu Kosan Co.), and 3-butoxy-N,N-dimethylpropionamide (Equamide B100, a product of idemitsu Kosan Co.).

[0071] The alcohol-based solvent may be at least one selected from methanol, ethanol, 1-propanol, 2-propanol (or isopropanol), 1-butanol, 2-methyl-1-propanol, 2-butanol, 1-methyl-2-propanol, pentanol, hexanol, heptanol, octanol, glycerol, trimethylolpropane, pentaerythritol, and sorbitol.

[0072] The diol-based solvent may be at least one selected from ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, and hexanediol.

[0073] The glycol ether-based solvent may be at least one selected from the group consisting of ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, and tetraethylene glycol monobutyl ether.

[0074] The ketone-based solvent may be at least one selected from the group consisting of acetone, methyl ethyl ketone, methyl propyl ketone, and cyclopentanone.

[0075] The ester-based solvent may be at least one selected from the group consisting of ethyl acetate, γ-butyrolactone, and ε-propiolactone.

[0076] In addition, the aqueous solvent may be water.

[0077] The carbon nanotube dispersion of the present invention comprising the above components has excellent dispersibility, low dispersion viscosity, and a small degree of increase in viscosity over time.

[0078] The viscosity of the carbon nanotube dispersion may be 1,000 cps to 15,000 cps, particularly 3,000 cps to 14,500 cps, and more particularly 5,000 cps to 14,300 cps, when measured using a viscometer (product of TOKI SANGYO Co., Viscometer TV-25) at 25° C. using a rotor 1 at 1 rpm. If the carbon nanotube dispersion has a viscosity within the range, an electrode slurry may be more easily prepared by using the same, and the electrode slurry including the carbon nanotube dispersion may have an appropriate viscosity for forming an electrode.

[0079] In addition, the viscosity of the carbon nanotube dispersion may be 2,000 to 16,000 cps, specifically 3,000 to 15,500 cps, and more specifically 5,000 to 15,000 cps, if measured using a viscometer (product of TOKI SANGYO Co., Viscometer TV-25) at 25° C. using rotor 1 at 1 rpm after 1 week from preparation.

[0080] Furthermore, the carbon nanotube dispersion may have a viscosity increase rate of 20% or less, specifically 10% or less, and more specifically 5% or less, after standing at 25° C. for 1 week.

[0081] Method for preparing carbon nanotube dispersion

[0082] Hereinafter, a method for preparing a carbon nanotube dispersion will be described. The method for preparing a conductive material dispersion according to the present invention includes: (1) mixing carbon nanotubes, a dispersant, and a dispersion medium to prepare a mixture; and (2) dispersing the mixture. Here, the dispersant includes a first dispersant and a second dispersant in a weight ratio of 100:10 to 100:90, the first dispersant is a dispersant containing N atoms, the second dispersant is a compound containing a sulfonic acid group, a hydroxyl group, and an aromatic ring in a molecular structure, and the weight ratio of the carbon nanotubes to the dispersant is 100:50 to 100:500.

[0083] In step (1), carbon nanotubes, a dispersant, and a dispersion medium are mixed to prepare a mixture.

[0084] The step for preparing the mixture may be performed under temperature conditions at which physical properties including the viscosity of the mixture are not changed by evaporation of the dispersion medium, for example, at 50°C or lower, more particularly 5°C to 50°C.

[0085] In step (2), the mixture is dispersed to prepare a carbon nanotube dispersion.

[0086] The dispersion can be performed by a grinding method using a ball mill, a bead mill, a disk mill, a basket mill and a high-pressure homogenizer, more particularly, by a grinding method using a disk mill or a high-pressure homogenizer.

[0087] During grinding with a bead mill, the size of the beads can be appropriately determined according to the type and amount of the carbon nanotubes and the type of the dispersant, and in particular, the diameter of the beads can be 0.1 mm to 5 mm, more particularly, 0.5 mm to 4 mm. In addition, the grinding process can be performed at a rate of 1,000 rpm to 15,000 rpm, more particularly, at a rate of 2,000 rpm to 12,000 rpm. The dispersion process can be performed according to the dispersion degree of the carbon nanotube dispersion, and can be performed for 30 minutes to 120 minutes, more particularly, 60 minutes to 90 minutes.

[0088] Grinding with a high pressure homogenizer can be carried out by, for example, pressurizing the mixture with a plunger pump of a high pressure homogenizer and pushing it through the gap of a homogenizing valve, and by the forces of cavitation, shearing, impact and explosion during the gap. The pressure of the high pressure homogenizer can be 5,000psi to 40,000psi, particularly 10,000psi to 30,000psi, more particularly 14,000psi to 25,000psi. Dispersion by a high pressure homogenizer can be carried out 1 to 15 times, particularly 2 to 10 times, more particularly 3 to 7 times.

[0089] Electrode slurry composition

[0090] In addition, the present invention provides an electrode paste composition for a lithium secondary battery, which comprises the carbon nanotube dispersion and an electrode active material.

[0091] The electrode paste composition for a lithium secondary battery may be a positive electrode paste composition or a negative electrode paste composition, particularly a negative electrode paste composition.

[0092] The electrode paste composition for a lithium secondary battery may comprise the carbon nanotube dispersion, a positive electrode active material or a negative electrode active material as the electrode active material, a binder (if necessary), a solvent, and / or other additives.

[0093] As the positive electrode active material, positive electrode active materials known in the art can be used without limitation, and for example, lithium cobalt-based oxides, lithium nickel-based oxides, lithium manganese-based oxides, lithium iron phosphate oxides, lithium nickel manganese cobalt-based oxides, or combinations thereof can be used. In particular, as the positive electrode active material, there are LiCoO 2 、LiNiO 2 、LiMn 2 O 4 、LiCoPO 4 、LiFePO 4 、LiNiaMnbCocO 2 (where 0 < a, b, c < 1), but there is no limitation.

[0094] As the negative electrode active material, at least one or at least two negative electrode active materials selected from the following may be included: carbonaceous materials such as natural graphite and artificial graphite; lithium-containing titanium composite oxides (LTO); metals (Me) such as Si, Sn, Li, Zn, Mg, Cd, Ce, Ni, and Fe; alloys composed of the metals (Me); oxides (MeOx) of the metals (Me); and composites of the metals (Me) and carbon. Based on the total weight of the solid content other than the solvent in the negative electrode paste, the negative electrode active material may be included in an amount of 60% by weight to 98% by weight, more preferably 70% by weight to 98% by weight.

[0095] The binder is a component that helps the binding between the active material and the conductive material and the binding with the current collector, and is usually added in an amount of 1% by weight to 30% by weight based on the total weight of the mixture containing the electrode active material. Examples of the binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers.

[0096] The solvent may be an organic solvent including N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, dimethylacetamide, etc., or water, and a mixture of one or two or more thereof may be used. Considering the application thickness and preparation yield of the slurry, the amount of the solvent may be sufficient as long as the electrode active material, the binder, and the conductive material are dissolved or dispersed.

[0097] The viscosity controller may be carboxymethyl cellulose, polyacrylic acid, or the like, and due to the addition thereof, the viscosity of the electrode slurry may be controlled so that the preparation of the electrode slurry and the coating process on the electrode current collector may be easy.

[0098] The filler is a component that suppresses electrode expansion and is selectively used, and any one that does not cause chemical changes to the battery and is a fiber material is used, but there is no particular limitation. For example, olefin-based polymers such as polyethylene and polypropylene; and fiber materials such as glass fiber and carbon fiber are used.

[0099] If the electrode slurry composition is a positive electrode slurry composition for forming a positive electrode, the composition of the positive electrode is applied to a positive electrode collector, dried and rolled to produce a positive electrode. Alternatively, the positive electrode slurry can be cast on a separate support, and then the film obtained by separating from the support can be laminated on the positive electrode collector.

[0100] The thickness of the positive electrode active material layer formed by the positive electrode slurry may vary according to a loading amount, a loading rate, etc. for applying the positive electrode slurry.

[0101] The thickness of the positive electrode collector may generally be 3 μm to 500 μm. The positive electrode collector may include a material having high conductivity without causing chemical changes to the battery, but is not particularly limited. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive electrode collector may enhance the bonding strength of the positive electrode active material by forming micro-embossings on the surface of the positive electrode collector, and various types including films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics may be used.

[0102] If the electrode slurry composition is a negative electrode slurry composition for forming a negative electrode, the composition of the negative electrode can be applied to a negative electrode collector, dried and rolled to produce a negative electrode. Alternatively, the negative electrode slurry can be cast on a separate support, and then the film obtained by separating from the support can be laminated on the negative electrode collector.

[0103] The thickness of the negative electrode active material layer formed by the negative electrode slurry may vary according to a loading amount, a loading rate, etc. for applying the negative electrode slurry.

[0104] The thickness of the negative electrode current collector can generally be 3 μm to 500 μm. The negative electrode current collector can use any one with high conductivity that does not cause chemical changes to the battery, but there is no particular limitation. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloy can be used. In addition, as with the negative electrode current collector, micro-embossing can be formed on the surface of the negative electrode current collector to enhance the bonding strength of the negative electrode active material, and various types including films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics can be used.

[0105] Lithium secondary battery

[0106] The lithium secondary battery includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode and the negative electrode are the same as above, a detailed description thereof will be omitted.

[0107] Separator is used to separate negative electrode and positive electrode, and is used to provide the mobile channel of lithium ion, and uses any separator used in general lithium secondary battery, but is not particularly limited, in particular, it is preferred that the separator has low resistance to the movement of electrolyte ions and has excellent electrolyte impregnation ability. In particular, porous polymer film can be used, for example, porous polymer film formed by polyolefin-based polymers such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer, or a laminated structure of both or more thereof. In addition, general nonwoven fabrics can be used, for example, nonwoven fabrics formed by high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a separator coated with and comprising a ceramic component or a polymer material for ensuring heat resistance or mechanical strength can be used, and selectively, a single layer or multilayer structure can be used.

[0108] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a melt inorganic electrolyte, etc., which may be used during the manufacture of a lithium secondary battery, but is not limited. In particular, the electrolyte may include an organic solvent and a lithium salt.

[0109] The organic solvent can use any one that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery, but there is no particular limitation. In particular, as the organic solvent, ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether-based solvents such as dibutyl ether and tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol-based solvents such as ethanol and isopropanol; nitrile such as R-CN (R is a hydrocarbon group of a linear, branched or cyclic structure of C2 to C20, and may contain a double bond, an aromatic ring or an ether bond); amide such as dimethylformamide; dioxolane such as 1,3-dioxolane; or cyclopentane sulfone. Among them, carbonate-based solvents are preferred, and a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ion conductivity and high dielectric properties for improving the charge and discharge performance of the battery and low viscosity linear carbonate-based compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, if the cyclic carbonate and the chain carbonate are mixed and used in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be exhibited.

[0110] The lithium salt may be any compound that can provide lithium ions used in a lithium secondary battery, but is not particularly limited. In particular, the lithium salt may be LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 、LiCl、LiI、LiB(C 2 O 4 ) 2The concentration of the lithium salt may be in the range of 0.1 M to 2.0 M. If the concentration of the lithium salt is within this range, the electrolyte may have appropriate conductivity and viscosity, thereby exhibiting excellent electrolyte performance, and lithium ions may be efficiently moved.

[0111] In the electrolyte, for the purpose of improving the life characteristics of the battery, suppressing the reduction of the battery capacity, and improving the discharge capacity of the battery, in addition to the constituent components of the electrolyte, one or more additives may be contained, for example, a halogenated alkylene carbonate-based compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride. In this case, the additive may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0112] In a lithium secondary battery including an electrode formed by using a carbon nanotube dispersion according to the present invention, in particular, in a lithium secondary battery including a negative electrode formed by using the carbon nanotube dispersion, carbon nanotubes are uniformly dispersed in the negative electrode, and the content thereof can be reduced compared to the case of including conventional conductive materials such as conductive carbon black, and the discharge capacity and output characteristics can be stably exhibited. Therefore, the lithium secondary battery can be used in portable devices such as mobile phones, notebook computers and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEV).

[0113] Therefore, a lithium secondary battery, a battery module including the lithium secondary battery as a unit battery, and a battery pack including the same may be provided.

[0114] The battery module or battery pack can be used as a power source for one or more large and medium-sized devices including: power tools; electric motor vehicles, including electric vehicles (EV), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEV); and energy storage systems.

[0115] Hereinafter, the embodiments will be described in detail to explain the present invention in detail. However, the embodiments are for illustrating the present invention, and the scope of the present invention should not be limited thereto.

[0116] Example

[0117] Example 1

[0118] 0.675 wt% of polyvinyl pyrrolidone (PVP K15, a product of Zhangzhou Huafu Chemical Co.), 0.225 wt% of sodium lignin sulfonate (Borregaard Co.) and water as a dispersion medium were mixed to prepare 497 g of a mixture. In a dissolver (VMA-Getzmann Co., Dispermat-CA), an impeller and a container were installed and rotated at 400 rpm for 10 minutes to mix the dispersant and the dispersion medium in the mixture.

[0119] 0.6 wt% of a specific surface area of ​​1,160 m 2 / g and a single-walled carbon nanotube (SWCNT, TUBALL, a product of OCSiAl Co.) having a length of 5 μm or more was prepared and dispersed at 8,000 rpm for 60 minutes.

[0120] The resultant was treated five times using a high pressure disperser (PICOMAX, Micronox Co.) at a pressure of 20,000 psi to prepare a carbon nanotube dispersion.

[0121] Example 2

[0122] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the polyvinyl pyrrolidone content was changed to 1.125 wt %, the sodium lignin sulfonate content was changed to 0.375 wt %, and the single-walled carbon nanotube content was changed to 1.0 wt %.

[0123] Example 3

[0124] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the polyvinyl pyrrolidone content was changed to 1.0 wt %, the sodium lignin sulfonate content was changed to 0.5 wt %, and the single-walled carbon nanotube content was changed to 1.0 wt %.

[0125] Example 4

[0126] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the polyvinyl pyrrolidone content was changed to 1.2 wt %, the sodium lignin sulfonate content was changed to 0.3 wt %, and the single-walled carbon nanotube content was changed to 1.0 wt %.

[0127] Example 5

[0128] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the polyvinyl pyrrolidone content was changed to 1.25 wt %, the sodium lignin sulfonate content was changed to 0.25 wt %, and the single-walled carbon nanotube content was changed to 1.0 wt %.

[0129] Comparative Example 1

[0130] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, sodium lignin sulfonate was not included and the polyvinyl pyrrolidone content was changed to 0.9 wt %.

[0131] Comparative Example 2

[0132] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the same content of tristyrylphenol ethoxylate was used instead of sodium lignin sulfonate.

[0133] Comparative Example 3

[0134] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the same content of styrene maleic acid copolymer was used instead of sodium lignin sulfonate.

[0135] Comparative Example 4

[0136] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, polyvinyl pyrrolidone was not included and the sodium lignin sulfonate content was changed to 0.9 wt %.

[0137] Comparative Example 5

[0138] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the polyvinyl pyrrolidone content was changed to 0.75 wt %, the sodium lignin sulfonate content was changed to 0.75 wt %, and the single-walled carbon nanotube content was changed to 1.0 wt %.

[0139] Comparative Example 6

[0140] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the polyvinyl pyrrolidone content was changed to 1.4 wt %, the sodium lignin sulfonate content was changed to 0.1 wt %, and the single-walled carbon nanotube content was changed to 1.0 wt %.

[0141] Comparative Example 7

[0142] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the same content of polyglycerol-3-diisostearate was used instead of polyvinyl pyrrolidone.

[0143] Comparative Example 8

[0144] A carbon nanotube dispersion was prepared by the same method as in Example 1, except that in Example 1, the same content of epicatechin gallate was used instead of sodium lignin sulfonate.

[0145] [Table 1]

[0146]

[0147] *PVP: Polyvinylpyrrolidone

[0148] *PG-3-DIS: Polyglyceryl-3-diisostearate

[0149] Experimental example

[0150] With respect to the carbon nanotube dispersions prepared in Examples 1 to 5 and Comparative Examples 1 to 8, the initial viscosity after dispersion and the viscosity after standing at 25° C. for 1 week were measured, and the results are shown in Table 2 below.

[0151] The viscosity was measured using a viscometer (TV-25, product of TOKI Co.) at 25°C using a rotor 1 at 1 rpm.

[0152] [Table 2]

[0153]

[0154] Referring to Table 2 above, it can be confirmed that the viscosity of the carbon nanotube dispersions in Examples 1 to 5 after standing at 25° C. for 1 week did not increase (Examples 1 and 2) or showed a low level (Examples 3 to 5). However, in the case of Comparative Examples 1 to 8, the carbon nanotube dispersions all showed a high viscosity increase rate after standing at 25° C. for 1 week after preparation.

[0155] Among them, although Comparative Examples 2, 3, and 8 are examples in which a second dispersant is used in addition to PVP as the first dispersant as in the examples, a significantly high viscosity increase rate and a high viscosity after the carbon nanotube dispersion is left to stand for 1 week at 25° C. are shown compared to Examples 1 to 5, and a high viscosity increase rate is shown even compared to Comparative Example 1 or 4 in which one type of dispersant is used. In addition, in the case of Comparative Example 7 in which a different type of first dispersant is used instead of PVP, the viscosity itself is high and the viscosity cannot be measured. It was thus determined that although two types of dispersants were used, the effect was changed depending on the type of dispersant.

[0156] In particular, it was confirmed that, if a compound containing a sulfonic acid group, a hydroxyl group, and an aromatic ring was applied as a second dispersant in addition to a dispersant containing an N atom as a first dispersant as in Examples 1 to 5, excellent dispersibility was exhibited and an increase in viscosity could be effectively suppressed, but, if a compound containing only a hydroxyl group and an aromatic ring (tristyrylphenol ethoxylate and epicatechin gallate) was applied as in Comparative Examples 2 and 8, or a compound containing only an aromatic ring was applied as in Comparative Example 3, no dispersibility improvement effect was exhibited. Also, in the case of Comparative Example 7 using the same second dispersant but using PG-3-DIS containing no N atom as a first dispersant, dispersion itself was not easy and the dispersant did not provide a sufficient degree of dispersibility.

[0157] Meanwhile, in the case of Comparative Example 5, the types of the first dispersant and the second dispersant are the same as those in Examples 1 to 5, and the injection amount of the dispersant relative to the CNT is the same, but the amount of the second dispersant relative to the first dispersant is excessive from the appropriate range, and the amount of the second dispersant is excessive. Therefore, the viscosity increase rate is shown at a level similar to or slightly higher than that of Comparative Example 1, and it can be determined that the amount ratio of the first dispersant and the second dispersant needs to satisfy an appropriate ratio.

[0158] In contrast to Comparative Example 5, in the case of Comparative Example 6, the amount of the second dispersant relative to the first dispersant is less than the appropriate range, and Comparative Example 6 also shows a high initial viscosity and a high viscosity increase rate, and it can be determined that only when the appropriate amount ratio of the first dispersant and the second dispersant is met can the target effect of the present invention be achieved.

Claims

1. A carbon nanotube dispersion comprising carbon nanotubes, a dispersant and a dispersion medium, wherein The dispersant comprises a first dispersant and a second dispersant in a weight ratio of 100:10 to 100:90, The first dispersant is a dispersant containing N atoms, the second dispersant is a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure, and The weight ratio of the carbon nanotubes to the dispersant is 100:50 to 100:

500.

2. The carbon nanotube dispersion according to claim 1, wherein the carbon nanotube has a specific surface area (BET) of 800 m 2 / g or greater. The carbon nanotube dispersion according to claim 1 , wherein the carbon nanotubes are single-walled carbon nanotubes. 4 . The carbon nanotube dispersion according to claim 1 , wherein the carbon nanotubes are included in an amount of 0.1 parts by weight to 5 parts by weight based on 100 parts by weight of the carbon nanotube dispersion.

5. The carbon nanotube dispersion according to claim 1, wherein the first dispersant is one or more selected from the group consisting of polyvinyl pyrrolidone, polyacrylic acid hydrazide, poly-N-vinyl-5-methyl Oxazolidinone, N-alkylpolyimine, N-acetylpolyimine, polyacrylamide, poly-L-lysine hydrobromide, benzyl-dodecyl-dimethylammonium chloride and polyethyleneimine. The carbon nanotube dispersion according to claim 1 , wherein the second dispersant is a lignin sulfonate compound. 7 . The carbon nanotube dispersion according to claim 1 , wherein the second dispersant is sodium lignin sulfonate, calcium lignin sulfonate, or a mixture thereof. 8 . The carbon nanotube dispersion according to claim 1 , wherein the dispersant comprises the first dispersant and the second dispersant in a weight ratio of 100:20 to 100:

80. 9 . The carbon nanotube dispersion according to claim 1 , wherein a weight ratio of the carbon nanotubes to the dispersant is 100:100 to 100:

300. 10 . The carbon nanotube dispersion according to claim 1 , wherein a weight ratio of the carbon nanotubes to the dispersant is 100:120 to 100:

250.

11. The carbon nanotube dispersion according to claim 1, wherein the dispersion medium is one or more selected from the group consisting of an amide-based polar organic solvent, an alcohol-based solvent, a glycol-based solvent, a glycol ether-based solvent, a ketone-based solvent, an ester-based solvent, and an aqueous solvent. 12 . The carbon nanotube dispersion of claim 1 , wherein the carbon nanotube dispersion has a viscosity of 1,000 cP to 16,000 cP. 13 . An electrode slurry composition for a lithium secondary battery, the composition comprising the carbon nanotube dispersion according to claim 1 and an electrode active material.

14. A method for preparing the carbon nanotube dispersion according to claim 1, the method comprising: (1) a step of mixing carbon nanotubes, a dispersant, and a dispersion medium to prepare a mixture; as well as (2) a step of dispersing the mixture, wherein The dispersant comprises a first dispersant and a second dispersant in a weight ratio of 100:10 to 100:90, The first dispersant is a dispersant containing N atoms, the second dispersant is a compound containing a sulfonic acid group, a hydroxyl group and an aromatic ring in the molecular structure, and The weight ratio of the carbon nanotubes to the dispersant is 100:50 to 100:500.

Citation Information

Patent Citations

  • Air rifle using electromagnetic valve

    KR1020230024182A

Cited By

  • Battery cell, method for producing the same, battery device, electric device, and energy storage device

    CN122716320A